2017
DOI: 10.1139/gen-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting morphological and DNA barcode-suggested species boundaries among shallow-water amphipod fauna from the southern European Atlantic coast

Abstract: In this study we compared DNA barcode-suggested species boundaries with morphology-based species identifications in the amphipod fauna of the southern European Atlantic coast. DNA sequences of the cytochrome c oxidase subunit I barcode region (COI-5P) were generated for 43 morphospecies (178 specimens) collected along the Portuguese coast which, together with publicly available COI-5P sequences, produced a final dataset comprising 68 morphospecies and 295 sequences. Seventy-five BINs (Barcode Index Numbers) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…com.). It is worth noting that similar results were recently observed in the case of some other North Atlantic amphipod species reported as having wide distribution range for six out of the 68 identified morphospecies (Lobo et al 2017). In their case study the incongruence between the morphological identification and genetic variability was explained by geographic distance in four of the disparate morphospecies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…com.). It is worth noting that similar results were recently observed in the case of some other North Atlantic amphipod species reported as having wide distribution range for six out of the 68 identified morphospecies (Lobo et al 2017). In their case study the incongruence between the morphological identification and genetic variability was explained by geographic distance in four of the disparate morphospecies.…”
Section: Discussionsupporting
confidence: 85%
“…The latter is commonly used for species delimitation in arthropods and particularly in Amphipoda (e.g. Hebert et al 2003, Costa et al 2007, 2009, Raupach et al 2015, Lobo et al 2017). Both uncorrected p-distance and K2P were used to calculate species distances.…”
Section: Methodsmentioning
confidence: 99%
“…Taking COI data as a benchmark for comparison of genetic distances among crustacean species (Costa et al, ; Lobo et al, ), even the shortest distances between D. edwardsi complex MOTUs (3.79%) would fall beyond the recorded distribution of intraspecific distances in numerous well‐established morphospecies, including this study's results for the other two congeneric species D. bidentata and D. magnitorata (maximum 1.54% and 2.65%, respectively; Table ). On the other hand, the highest average distance observed between the nine MOTUs within D. edwardsi complex (21.92%) surpasses the average distance between D. bidentata and D. magnitorata (16.55%).…”
Section: Discussionmentioning
confidence: 75%
“…Studies addressing the biology of Hyalidae are scarce (Dubiaski‐Silva & Masunari, ; Hiwatari & Kajihara, ; Tsoi & Chu, ), and in the NEA focused mostly on habitat and food preferences (Guerra‐García, Ros, Izquierdo, & Soler‐Hurtado, ; Torrecilla‐Roca & Guerra‐García, ; Vinagre et al, ). The only Hyalidae species investigated in NEA from the genetic viewpoint was Apohyale prevostii (Lobo et al, ; Raupach et al, ), but no molecular data were previously reported for the Macaronesia region.…”
Section: Introductionmentioning
confidence: 99%